Bees, beekeepers, and bureaucrats: parasitism and the politics of transgenic life - Lezaun, J (2011)
Over the last decade the flying patterns and foraging behavior of bees have become a matter of public policy in the European Union. Determined to establish a system where transgenic crops can `coexist' with conventional and organic farming, the EU has begun to erect a system of demarcations and separations designed to minimize the extent of `gene flow' from genetically modified plants. As the European landscape is regimented through the introduction of isolation distances and buffer zones, bees and other pollinating insects have become vectors of `genetic pollution', disrupting the project of cohabitation and purification devised by European authorities. Drawing on the work of Michel Serres on parasitism, this paper traces the emergence of bees as an object of regulatory scrutiny and as an interruptor of the `coexistence' project. Along with bees, however, another uninvited guest arrived unexpectedly on the scene: the beekeeper, who came to see his traditional relationship to bees, crops, and consumers at risk. The figure of the parasite connects the two essential dynamics described in this paper: an escalation of research and the intensification of political attributes.